Islamic revivalism in Malaysia : an Islamic response to non-muslim concerns - Yousif, Ahmad (Association of Muslim Social Scientists, 2004)
This article briefly reviews some of the causes, manifestations and effects of the growing Islamic revivalism in Malaysia. Secondly, it examines the concerns of non-Muslim minorities about this rising Islamic consciousness, including an Islamic response to such concerns. Finally, the extent to which the events of September 11th, 2001 have changed the dynamics between ethno-religious minorities and the government briefly be assessed.